2019
DOI: 10.1177/1933719118799202
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Maternal Age With Fetal Growth and Newborn Measures: The Mumbai Maternal Nutrition Project (MMNP)

Abstract: Background: Young maternal age is associated with poorer birth outcomes, but the mechanisms are incompletely understood. Using data from a prospective cohort of pregnant women living in Mumbai slums, India, we tested whether lower maternal age was associated with adverse fetal growth. Methods: Fetal crown-rump length (CRL) was recorded at a median (interquartile range, IQR) of 10 weeks’ gestation (9-10 weeks). Head circumference (HC), biparietal diameter (BPD), femur length (FL), and abdominal circumference (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…In our study, at the same time, younger and older age was associated with higher adjusted odds ratios of PE, IUGR, and preterm birth <37th week, which is consistent with reports in the literature [17][18][19]32], but the number of PE (n = 24) and IUGR (n = 21) cases in our the cohort was small. PE and IUGR often coexist, and in their pathogenesis the role of placental ischemia in early pregnancy is taken into account.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, at the same time, younger and older age was associated with higher adjusted odds ratios of PE, IUGR, and preterm birth <37th week, which is consistent with reports in the literature [17][18][19]32], but the number of PE (n = 24) and IUGR (n = 21) cases in our the cohort was small. PE and IUGR often coexist, and in their pathogenesis the role of placental ischemia in early pregnancy is taken into account.…”
Section: Discussionsupporting
confidence: 92%
“…Our core results (higher risk of pregnancy complications in older mothers, and associations of young age with some pregnancy outcomes) are consistent with several reports in the world literature [4,[17][18][19][20][21]28]. However, some studies have found no correlation between maternal age and pregnancy outcomes [2,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study examined individual and community effects on advanced maternal age pregnancy, a growing phenomenon with serious implications for maternal, neonatal and child morbidity and mortality [30,[16][17][18][19][20]. The study improved upon previous studies by examining the individual and contextual effects on AMA pregnancy which were largely ignored in most existing hospital-based studies [21-23, 25, 2, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Two, the proportion of women delaying motherhood for the purpose of achieving education and career enhancement is steadily increasing in the country [15]. Irrespective of the reasons for AMA pregnancy across the world, AMA pregnancy is a safe motherhood issue worthy of further investigation because evidence abounds that AMA pregnancy elevates the risks of maternal, neonatal and child mortality [16][17][18][19][20]. In a number of countries, numerous studies have examined different aspects of AMA pregnancy [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%